Fuzzy Inventory Model for Deteriorating Items With Low Carbon Emission Cost Under Preservation Technology and Trade Credit - Hemalatha, S.; Annadurai, K. (Communications in Mathematics and Applications, 2023)
Organizations are eager on rethinking and optimizing their current stock techniques in order to achieve profitability. When managing a supply chain, the phenomenon of deterioration becomes a major consideration. It is able to control the expenditure incurred on preservation technology for deteriorating things up to a specified limit. Nowadays, the world’s consciousness is to reduce carbon footprints to mitigate global warming. Consumers have become cognizant of surroundings protection and like low carbon evolved products. We explore a mathematical model for the retailer under the conditions of permissible delay in payments; thereby trade credit is implemented to draw customers. In this study, a crisp model is evolved to reduce the total cost. However, parameters are obscure. To model this impreciseness, a fuzzy model is taken into consideration by taking the parameters as triangular fuzzy numbers. Total cost function is defuzzified through Signed-distance method and is proven to be convex. Comparison of crisp and fuzzy models via special cases is carried out. Moreover, sensitivity analysis and graphical representation are given. Finally, the model obtains the minimal supply chain cost with decision variables as confirmed through the numerical study.
Keywords: Trade credit; Preservation technology investment; Carbon emission; Triangular fuzzy number; Signed distance method